Gifted Education, Creativity and Leadership Development - Sisk, Dorothy (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In these uncertain and challenging times, we need to help gifted students find their purpose and work toward finding a passion in their work and life. These new perspectives are both brilliant and practical and represent a synthesis of wisdom and experience. The new perspectives address the need to identify and nurture diverse students using scenarios and simulations and an active involvement in observing differentiation to learn how to identify and serve gifted students. We have unpreceded opportunity, with access to technology, to engage in collaborative research and program development across disciplines and internationally. In conclusion, there is deep wisdom here for gifted students, their parents and teachers, who can all benefit from exploring these new perspectives.